Effect of nitrogen, phosphorus, and potassium doses on tree tomato (Solanum betaceum Cav.) growth in the vegetative phase - Ramírez-Soler, Claudia Helena; Magnitskiy, Stanislav; Melo M., Sandra Esperanza; Melgarejo, Luz Marina (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
The objective of this study was to evaluate the effects of nitrogen, phosphorus and potassium doses on tree tomato (Solanum betaceum Cav.) growth in the vegetative phase. This research was conducted under greenhouse conditions at the National University of Colombia, Bogotá. A randomized block design was employed to evaluate eight treatments with three replicates as follows: i) CC: commercial control, ii) CS: control without fertilization, iii) Low N: 10% of the recommended dose (DR); iv) Low P: 10% DR; v) Low K: 10% DR, vi) High N: 200% DR; vii) High P: 200% DR, and viii) High K: 200% DR. The fertilizer plan was adjusted according to the soil analysis and doses reported for the species. To determine plant growth, growth rate indexes were used based on the functional logistic model. The treatment without fertilization CS and High P reduced the leaf area, number of leaves, stem length, and dry mass of leaves of the tree tomatoes by about 50%, unlike the commercial control (CC). The Low K treatment increased the same variables by 70%, as well as the total dry mass. For growth rates, the Low K treatment resulted in the highest leaf area index and relative growth rate, and the High K treatment presented the highest crop growth rate.